TEKNOLOGI PENANGANAN DAN PENGAWETAN DI ATAS KAPAL PADA NELAYAN KABUPATEN ACEH BARAT - Ikhsanul Khairi; Nabila Ukhty; Nurul Najmi; Mira Mauliza Rahmi; Heriansyah Heriansyah; Samsul Bahri; Yasrizal Yasrizal (Jurnal Marine Kreatif, 2021)
Fish handling and preservation  techniques are important things that must be applied in the fisheries industry. The purpose of this handling and preservation is to maintain the quality of the fish until it reaches the consumer. Handling activities must be carried out from upstream and downstream, namely from fishing activities to processing into products. Proper and good handling and preservation could produce prime commodities, high selling value, and expand market   access.  This  indirectly   has  the  potential   to  increase  fishermen’s   income.  The socialization  activity  was carried  out in the hall of the Department  of Marine  Affairs  and Fisheries (DKP) of West Aceh Regency. The purpose of this activity is to provide fishermen with an understanding of how to properly handle fish on board and preservation techniques that can be applied on board. The socialization  was held in two sessions. The first session presented  onboard handling technology  and the second session preservation  technology  on board. The socialization activity was closed with a discussion session with the fishermen, in this session a lot of information was received from fishermen regarding conditions in the field, so that it could be input in finding the best solution for fishermen in West Aceh. One solution given is to redesign the hatch space by adding aluminum foil to the insulator of the hatch so that it can be used optimally and pay more attention to the ratio of the amount of ice and fish during storage on the boat so that it can maintain the quality of the fish until the fish is landed.